2018
DOI: 10.1556/2006.7.2018.100
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting profiles of compulsive sexual behavior among adolescents

Abstract: Background and aimsThis two-study research was designed to define and predict profiles of compulsive sexual behavior (CSB) among non-clinical population of adolescents, and aimed to fill gaps in the current research.MethodsIn Study 1 (N = 1,182), we examined the profiles of CSB among adolescents using latent profile analysis. Results revealed the following three clusters: abstainers, sexual fantasizers, and individuals with CSB. In Study 2 (N = 618), we replicated this classification and examined differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 67 publications
(77 reference statements)
4
45
0
4
Order By: Relevance
“…Through this method, 10.12 and 7.81% of participants in two independent samples were identified as potentially suffering from CSBD. These figures are similar to those reported in adolescents through a similar data-driven approach (Efrati & Gola, 2018b) or in adults through different screening methods (Dickenson, Gleason, Coleman, & Miner, 2018;Giordano & Cecil, 2014;L angstr€ om & Hanson, 2006;Rettenberger et al, 2015;Skegg, Nada-Raja, Dickson, & Paul, 2010), but higher to those found through more clinically reliable assessment methods (Odlaug et al, 2013;e.g., structured interviews, Odlaug & Grant, 2010). A potential explanation for this increased prevalence is that our cluster approach captured not only clinically relevant levels of CSBD, but also subclinical manifestations of this condition (i.e., people displaying problematic but nonclinical out-of-control sexual behaviors that are nonetheless often accompanied by relevant levels of impairment and distress).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Through this method, 10.12 and 7.81% of participants in two independent samples were identified as potentially suffering from CSBD. These figures are similar to those reported in adolescents through a similar data-driven approach (Efrati & Gola, 2018b) or in adults through different screening methods (Dickenson, Gleason, Coleman, & Miner, 2018;Giordano & Cecil, 2014;L angstr€ om & Hanson, 2006;Rettenberger et al, 2015;Skegg, Nada-Raja, Dickson, & Paul, 2010), but higher to those found through more clinically reliable assessment methods (Odlaug et al, 2013;e.g., structured interviews, Odlaug & Grant, 2010). A potential explanation for this increased prevalence is that our cluster approach captured not only clinically relevant levels of CSBD, but also subclinical manifestations of this condition (i.e., people displaying problematic but nonclinical out-of-control sexual behaviors that are nonetheless often accompanied by relevant levels of impairment and distress).…”
Section: Discussionsupporting
confidence: 85%
“…This procedure is particularly advised in research contexts, where a large number of participants should be assessed in a limited time frame and classification as sexually compulsive or not occurs post hoc. A recent study by Efrati & Gola (2018b) satisfactorily identified adolescents with CSBD (12 and 14% of two independent samples) through a data-driven approach (Latent Profile Analyses, LPA). Internal and external validity of this cluster approach was demonstrated by analyzing psychosexual profile of adolescents in the CSBD cluster (characterized by an external locus of control, anxious attachment, greater loneliness, higher frequency of pornography use, and more online sexual activities).…”
Section: Main Approaches In the Identification And Classification Ofmentioning
confidence: 99%
“…Gender differences were also found in studies of Efrati and Gola 63 on a sample of 1800 Israeli adolescents (841 teen boys and 959 teen girls aged 14-18 years). The authors, using a latent profile analysis, revealed three clusters of CSB: abstainers, sexual fantasizers, and individuals with CSB (based on criteria of HD).…”
Section: N = 548mentioning
confidence: 66%
“…In the context of the prevalence of CSB, research indicated that fewer women (as compared to men) reported viewing pornographic materials over the last 6 months, 44 they reported less pornography time use 44,[46][47][48]77 and exhibited lower rates of feeling urges to pornography, 45 a smaller percentage of them self-identified as addicted to pornography based on subjective feeling, 14 and fewer women reported symptoms related to CSB, such as difficulties in controlling sexual thoughts and behaviors, engaging in sexual activity to cope with unpleasant emotional states, and experiencing negative consequences because of these sexual behaviors. [50][51][52][53][55][56][57]63,75,77,89,90,109,111,134,136 It is worth noting that prior research focused on measuring PPU and masturbation and has been conducted almost exclusively in men, and prior work has not included a deeper analysis of patterns of sexual functioning of women who reported issues related to CSB. We also note that the subjective assessment of addiction to pornography does not necessarily reflect a CSBD diagnosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…In the addiction context it has been shown that individuals with more symptoms show less emotional empathy (Ferrari, Smeraldi, Bottero, & Politi, 2014). Also problematic IP use has been associated with socio-emotional problems (Efrati & Gola, 2018;Tonioni et al, 2018). Accordingly, it might be possible that the processing of pornographic images was less intense due to the reduced processing of socio-emotional signs in the pornographic images which may be the reason why less resources of the left IFG were needed.…”
Section: Discussionmentioning
confidence: 99%